Iron-mediated removal of ammonia from strong nitrogenous wastewater of food processing - Ivanov, Volodymyr M.; Wang, J.-Y.; Stabnikova, Elena; Krasinko, Victoria; Stabnikov, Victor; Tay, Stephen; Tay, Joo (My University, 2004)
The combination of microbial reduction and further microbial oxidation of iron was applied to the treatment of food-processing wastewater and recovery of ammonium. Fe2+ ions were formed by iron-reducing bacteria under anaerobic conditions. Ammonium was recovered by co-precipitation with negatively charged iron hydroxides produced during oxidation of Fe2+ by iron-oxidizing bacteria under microaerophilic conditions. The value-added by-product of this process can be used as a slowly released ammonium fertilizer.
Keywords: ammonium; iron-oxidizing bacteria; nitrogenous wastewater; iron-reducing bacteria; амоній; залізо-окислюючі бактерії; добриво амонійне; стічні води; кафедра біотехнології і мікробіології